Pembuatan healthy fruity-veggie gummy berbahan dasar buah naga dan sayur bayam untuk cegah stunting anak usia dini - Rizka Wulandari Putri; Rahmatullah Rahmatullah; Sri Haryati; David Bahrin; Asyeni Miftahul Jannah; Rizza Fadilah Fitri; Alek Al Hadi; Fauztin Zuraida Rizqi (CV Rezki Media, 2026)
Stunting remains a major nutritional challenge among Indonesian children and requires community-based interventions that promote healthy dietary practices. This community service program aimed to improve the knowledge and skills of members of the Rumah Cinta Dahlia Family Welfare Movement (PKK) in producing healthy gummies made from dragon fruit (Hylocereus polyrhizus) and red spinach as an alternative nutritious snack to support stunting prevention among children. The program involved nutrition education, practical training in gummy production, and evaluation through pre- and post-tests. A total of 46 PKK members participated in the activity. During the training, participants learned how to use lemon and citric acid as preservatives. The resulting gummies were then evaluated for texture, taste, aroma, appearance, shelf life, and consumer preference. The gummy production process involved mixing dragon fruit juice, red spinach extract, gelatin, and preservative agents, followed by molding and refrigerated storage for 35 days. The results showed that the proportion of participants with high knowledge increased from 65% before the intervention to 100% after the training. Sensory evaluation indicated that gummies preserved with lemon were preferred by 70% of participants, while 30% preferred those preserved with citric acid. The findings indicate that lemon may serve as a suitable natural preservative with good consumer acceptance and storage stability. Overall, the program successfully improved participants’ knowledge and practical skills in preparing nutritious food products and demonstrated the potential of dragon fruit and red spinach gummies as an innovative snack to support household-level stunting prevention efforts.